To Be with or Not: Emotional Causality and Afrikaans Prepositional met and van Constructions. Issue 2 (4th May 2021) - Bergh, Luna
Abstract: The objective of this article is to consider the Afrikaans prepositions met (with) and van (of) in relation to emotional causality from a cognitive linguistics perspective. The inquiry opens with the question of how a cognitive linguistics analysis that proceeds from reference points can capture the patterned use of the Afrikaans preposition met and van in relation to other aspects of proximity relationships, specifically the causal experience of emotion and companionship. Although met can manifest a precise merged point in time and space, for concomitant causation concerning responses to emotions in Afrikaans, a construction such as bewe van vrees/angs (tremble with fear/anxiety) employs the preposition van, as would be the case in other causal constructions of the same form, such as bewe van die koue (tremble with cold), and so emphasises intersections between companionship, containment, causality, circumstances, and possession.